If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + -2)(7x + 3) = 0 Reorder the terms: (-2 + 9x)(7x + 3) = 0 Reorder the terms: (-2 + 9x)(3 + 7x) = 0 Multiply (-2 + 9x) * (3 + 7x) (-2(3 + 7x) + 9x * (3 + 7x)) = 0 ((3 * -2 + 7x * -2) + 9x * (3 + 7x)) = 0 ((-6 + -14x) + 9x * (3 + 7x)) = 0 (-6 + -14x + (3 * 9x + 7x * 9x)) = 0 (-6 + -14x + (27x + 63x2)) = 0 Combine like terms: -14x + 27x = 13x (-6 + 13x + 63x2) = 0 Solving -6 + 13x + 63x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -7x)(2 + -9x) = 0Subproblem 1
Set the factor '(-3 + -7x)' equal to zero and attempt to solve: Simplifying -3 + -7x = 0 Solving -3 + -7x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -7x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -7x = 0 + 3 -7x = 0 + 3 Combine like terms: 0 + 3 = 3 -7x = 3 Divide each side by '-7'. x = -0.4285714286 Simplifying x = -0.4285714286Subproblem 2
Set the factor '(2 + -9x)' equal to zero and attempt to solve: Simplifying 2 + -9x = 0 Solving 2 + -9x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -9x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -9x = 0 + -2 -9x = 0 + -2 Combine like terms: 0 + -2 = -2 -9x = -2 Divide each side by '-9'. x = 0.2222222222 Simplifying x = 0.2222222222Solution
x = {-0.4285714286, 0.2222222222}
| 8n-3=13 | | (10q-3)(q+11)=0 | | 4x+9(36)=36 | | 4=39-9y | | 12=6+2n | | 3(2x-1)+(x-3)=0 | | x(x-9)=15 | | 8=2x-5 | | 6x-75x=100 | | (3q-2)(q-7)=0 | | 3/7x=21 | | 4x^2-44x+112= | | (3p-2)(q-7)=0 | | 1/7/8/9 | | 3x+35x=76 | | 12x=2x | | -2+1=3x-5 | | 2/5h-7=12/5h-2h | | w+1/5=7/8 | | (9p-4)(p+9)=0 | | 8=4m-4 | | 4+(-3/5)x=16 | | n/0.6=662/3 | | 2p^3+30p^2-68p= | | 86-2x=60 | | 3/2X5/8 | | v+v+v+v+v+10= | | (8x)+(11x-1)=180 | | x-0.7=8.52 | | 11/2*5/8 | | 6x-21=-12+9x | | P+7/4=37/8 |